Effects of an intermittent exercise fatigue protocol on biomechanics of soccer kick performance - Kellis, E.; Katis, A.; Vrabas, I. S. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The purpose of this study was to examine the effects of fatigue on biomechanical indices of soccer kick performance. Ten male amateur soccer players performed maximal instep kicks prior to, in the middle and after the implementation of a 90 min intermittent exercise protocol. Three-dimensional data, ground reaction forces (GRFs) and segmental moments were measured during the kick while blood lactate and ammonia concentrations were monitored throughout the protocol. Analysis of variance designs with repeated measures indicated a significant increase in ammonia (P<0.01) and lactate levels (P<0.01) following fatigue. The GRFs and joint displacement curves during the kick remained unaltered after fatigue (P>0.01). However, post-fatigue maximum angular velocity of the shank, the net moments acting on the shank and the resultant joint moments were significantly lower compared with the corresponding pre-exercise values (P<0.01). The velocity of the ball was 24.69 m/s prior to the protocol and significantly decreased to 21.78 m/s after (P<0.01). Similarly, the ball/foot speed ratio significantly (P<0.01) declined from 1.40±0.12 (pre-fatigue) to 1.33±0.18 (post-fatigue). The present results suggest that an exercise protocol that simulates soccer game conditions results in significant impairment of soccer kick performance. This could be attributed to alterations of the function of the neuromuscular system and force generation capacity, which may have altered the mechanics of soccer kick performance.